CREATIVITY IN MANAGEMENT OF TRANSPORT ENTERPRISE - JANA DICOVÁ; JÁN ONDRUŠ (Annals of the University of Petrosani: Economics)
The ability of modern enterprise management means to take advantage of unexpected change promptly and better as competition. The function of management in transport is to know dominates the internal and external processes thus the transport enterprise has the success in this environment. Transport management concentrates on assessments of measures of the requirement for convenient transport, the requirements for a particular type of transport and transport service and maintaining the existing market for transport. So transport management examines present situation of transport market and also orientation of next demand trends and opportunities of customer satisfy requirement. The papers deals about implementation of creativity in transport management, which connects with all processes of change that bring a lot of unknown and which present uncertainty, risk and growing potential for conflicts.